Cromatografia quiral em escala preparativa: estudo de casos e aplicação - Lourenço, Tiago de Campos (2012)
Different types of preparative chromatography techniques were applied to the enantiomeric purification of a series of chiral drugs. The efficiency of multicolumn chromatography with variable zones (VARICOL®) process and also the application for the resolution of drugs modafinil, atenolol and albendazole sulfoxide were investigated and is fully discussed in this work. The initial conditions for the separations were determined by theoretical simulation, using the software HELP 10.3 by Novasep®. For the modafinil separation, different feed concentrations were evaluated for the same zone distribution and period. The most efficient process provided 96.0% of enantiomeric purities for both enantiomers with a production rate of 2.24 g/dia. The enantiomers of albendazole sulfoxide were separated by the VARICOL® process, and the enantiomeric purities obtained were of 99.5% and 99.0% for rafinate and extract, respectively, with a production rate of, approximately, 2.0 g/dia. For both developed method, the mobile phase used was exclusively methanol, which was recovered around 95 %. Atenolol was efficiently enantiorresolved by CHIRALCEL OD®, however, the enantiomers were not obtained with high purities by the VARICOL® process due to their low solubility in the mobile phase and the high cycle time. This work describes also, for the first time, the absolute configuration of albendazole sulfoxide as (−)-(S) and (+)-(R)- enantiomers.To this end, vibrational circular dichroim and theoretical calculations were applied. The albendazol sulfoxide enantiomers were used for In Vitro tests against Taenia Solium cysts, the macroscopic, the microscopic and the biochemical behavior for the cysts were evaluated; (+)-(R)-albendazole sulfoxide was the enantiomer with the highest anthelmintic effect. Elution chromatography was used for the resolution of 3,4-methylenedioxymethamphetamine (MDMA) and omeprazole. MDMA was separated by the use of recycling in mass overload conditions, enantiomeric purities of 99.0% and 96.0% were obtained for (R)-(-)- and (S)-(+)- MDMA, respectively, with production rate of 40.0 mg/mL. Racemic MDMA and both enantiomers were used to evaluate oxidative stress status parameters. The enantiomers showed distinct effects in the liver redox state with the (R)-(−)- enantiomer being the responsible for the highest oxidative damage. For omeprazole separation, stack injections with mass overload was used, a production rate of 1.10 g/dia and high enantiomeric purities (99.0%) were attained and for this process, furthemore the mobile phase was totally recycled.